Purchase Channels and Motivation for Exercise in the Slovenian Population: Customer Behavior as a Guarantee of Fitness Center Sustainability - Vojko Vuckovic; Ivan Cuk; Sasa Duric (Behavioral Sciences, 2023)
The sustainability of fitness centers depends on two factors: member recruitment and retention, which is why these factors have received attention in recent decades. Temporal trends in fitness center membership purchase channels from 2016 to 2022 and motivation for exercise in 2022 in the Slovenian general population were investigated. The sample included 3419 participants, including 3131 participants (age 31.03 ± 11.31 years, 1430 females) and 288 participants (age 29.39 ± 10.43 years, 110 females) for the first and second objectives, respectively. Data were assessed using a web-based recruitment questionnaire and the EMI-2 motivation questionnaire. Traditional advertising strategies such as radio and flyers are the least effective (only 0.9% of memberships in 2022), while more sophisticated advertising strategies such as the internet and social media are becoming increasingly important in the advertising world (26.6% of memberships in 2022). On the other hand, word of mouth is the most influential method, attracting 51.3% of new members. Females, older members, and Eastern Slovenians were more motivated to exercise by health and esthetic motives, and males and younger members by challenge and competition. Fitness center management should focus on providing the best possible quality of service, tailoring it to the age, gender, and motivation of customers.